On Leap Reduced Reciprocal Randic and Leap Reduced Second Zagreb Indices of Some Graphs - Fazal Dayan; Muhammad Javaid; Muhammad Aziz ur Rehman (Scientific Inquiry and Review, 2019)
Naji et al. introduced the leap Zagreb indices of a graph in 2017 which are new distance-degree-based topological indices conceived depending on the second degree of vertices. In this paper, we have defined the first and second leap reduced reciprocal Randic index and leap reduced second Zagreb index for selected wheel related graphs.